A pilot study: Can shear wave elastography predict fatty infiltration of the supraspinatus muscle?. Issue 3 (6th August 2020) - Mackintosh, Stephen; Young, Adrienne; Muirhead, Jill; Lee, Arier; Sim, Jenny Hiow Hui
Abstract: Introduction: Significant fatty infiltration of the supraspinatus muscle is an important prognostic indicator for the likelihood of supraspinatus tendon repair failure. Two‐dimensional shear wave elastography (2D‐SWE) has the ability to quantitatively assess muscle stiffness. Presented is a pilot study comparing 2D‐SWE with the gold standard of magnetic resonance imaging (MRI) fatty infiltration grading. Methods: 2D‐SWE measurements were prospectively obtained in 152 shoulders of participants presenting for shoulder MRI examinations. 2D‐SWE measurements were obtained in the anterior and posterior aspects in the superficial half of the supraspinatus muscle and compared to MRI Goutallier grading of fatty infiltration as assessed by three observers. Region of interest measurements were placed within the elastogram (a) randomly, (b) at the highest colour‐coded region, and (c) within the most common colour code. Results: t ‐test reveals a statistically significant difference ( P = .002) between the mean of eight randomly placed 2D‐SWE samples with Goutallier 1 (mean shear wave speed [SWS] = 2.49) and 2 (mean SWS = 2.24). Although the difference was statistically significant, the large overlap of the SWS distributions between Goutallier grades 1 and 2 indicates that SWS is a poor predictor of Goutallier grading. Conclusion: Random SWS sampling throughout the superficial supraspinatus muscle highly correlates with MRI Goutallier grading but lacks accuracy.